A Community-Supported Clinic-Based Program for Prevention of Violence against Pregnant Women in Rural Kenya - Janet M. Turan; Abigail M. Hatcher; Merab Odero; Maricianah Onono; Jannes Kodero; Patrizia Romito; Emily Mangone; Elizabeth A. Bukusi (AIDS Research and Treatment)
Objective. Pregnant women are especially vulnerable to adverse outcomes related to HIV infection and gender-based violence (GBV). We aimed at developing a program for prevention and mitigation of the effects of GBV among pregnant women at an antenatal clinic in rural Kenya. Methods. Based on formative research with pregnant women, male partners, and service providers, we developed a GBV program including comprehensive clinic training, risk assessments in the clinic, referrals supported by community volunteers, and community mobilization. To evaluate the program, we analyzed data from risk assessment forms and conducted focus groups (n=2 groups) and in-depth interviews (n=25) with healthcare workers and community members. Results. A total of 134 pregnant women were assessed during a 5-month period: 49 (37%) reported violence and of those 53% accepted referrals to local support resources. Qualitative findings suggested that the program was acceptable and feasible, as it aided pregnant women in accessing GBV services and raised awareness of GBV. Community collaboration was crucial in this low-resource setting. Conclusion. Integrating GBV programs into rural antenatal clinics has potential to contribute to both primary and secondary GBV prevention. Following further evaluation, this model may be deemed applicable for rural communities in Kenya and elsewhere in East Africa.